2015
DOI: 10.22267/rcia.153202.13
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del compost y lombriabono sobre el crecimiento y rendimiento de berenjena Solanum melongena L.

Abstract: RESUMENLa berenjena se cultiva de manera convencional en la región Caribe colombiana, con una alta demanda de insumos agrícolas. No se reporta aún la implementación del manejo ecológico del cultivo para mejorar la competitividad de este sistema de producción. Ante esta problemática, se evaluó el efecto de la fertilización con abonos orgánicos sobre el crecimiento y rendimiento del cultivo de la berenjena Solanum melongena L. en el valle medio del río Sinú. El experimento se realizó en el primer semestre de 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…The growth of tomato and melon plants was significantly influenced by each of the different concentrations of humic acids in the fertilizer medium. The tomato plant presented a similar behavior in a study carried out by Rodríguez (2019, reported by Cantero et al, 2015). Various studies demonstrate the importance of the use of bioactive substances.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The growth of tomato and melon plants was significantly influenced by each of the different concentrations of humic acids in the fertilizer medium. The tomato plant presented a similar behavior in a study carried out by Rodríguez (2019, reported by Cantero et al, 2015). Various studies demonstrate the importance of the use of bioactive substances.…”
Section: Resultssupporting
confidence: 74%
“…It is estimated that approximately a quarter of the molecular weight of the humic substances is due to the oxygenated groups, mainly carboxylic groups that increase with the degree of humification of the organic matter and that can form carboxylates with metals present in the medium, phenolic groups that they form in the initial stages of humification and carbonyls groups that by oxidation reactions form carboxylic groups (Fischer, 2017;Gomes De Melo et al, 2016;Cantero et al, 2015;Pédrot and Mélanie, 2010). Humic substances play a very important role in nature; this is due to their present oxygenated functional groups, and they can participate in cation retention processes that are essential for plants as well as retaining heat on the surface due to their dark color (Pédrot and Mélanie, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the crucial advances in the generation of knowledge at the local and regional level for the cultivation of eggplant in areas, such as the production of planting material and substrates (Aramendiz et al, 2013), water requirements (Sánchez et al, 2004), weed management Hernández et al, 2015), nutrition (Cantero et al, 2015), phytosanitary management Jaramillo, 2006, 2013;Gómez et al, 2012), planting densities (Pérez et al, 2006), agronomic crop management (Aramendiz et al, 2008;Tapia et al, 2015), postharvest (Escobar et al, 2011) and new eggplant cultivars (Aramendiz et al, 2011;Cadena et al, 2011aCadena et al, , 2011b, the adoption of these technologies may be limited by the high level of illiteracy among producers, mainly in the G I , G II and G III groups, showing a level of illiteracy of around 50%, 67% and 16%, respectively (Tab. 2).…”
Section: Discussionmentioning
confidence: 99%
“…El actual ritmo de crecimiento de la población mundial es notorio, asociado a una mayor demanda de alimentos, que ha provocado el uso desmedido de los recursos naturales en especial del suelo que sufre modificaciones que conllevan a impactos negativos en la sostenibilidad de los sistemas productivos [1]. Es decir, el uso intensivo e indiscriminado de los fertilizantes de síntesis química con alta concentración de nutrientes en el suelo ha provocado un desequilibrio en sus propiedades físicas, químicas y biológicas [2] [3].…”
Section: Introductionunclassified